City Branding Againts Climate Change and Health Disruption in Prone Region: Initial Study From Semarang Citizen’s Dealing With Specific Waste Management on Pandemic Covid-19. - Maryono Maryono; Hartuti Purnaweni; Agus Junaedi; Glory Nasarani; Lintang Noor Prassanty; Handri Setiawan; Moch Rifky Pradita; Diana Rizky; Muhammad Dzaky Tagyuddin (Jurnal Ilmu Lingkungan, 2023)
City branding has been explored worldwide, in both academic reserch and policy practis of   regional and urban development. It is not only for attract invesment, toursm, sport but it is also to addresing identity and culturism. However, post pandemic-covid -19, and facing the climate hazard, resilience combining with healty cities need reshaping. For those, in the digital era, it is need a simple but fundamental incicators. This study examine citizen’s understanding, attitude and behavioral on the spesific waste management to deal with, as the entry point to analysis citizen capacity to participate on more complex action againts climate  adaptation and building healty life. Four component citizen action is measured; 1) creativities in regulation,3) citizen understanding, attitude on covid-19 waste daily handling and 4) potensial environmental risk. The area of study selected in Semarang as of 100RC network. Result of study show that event the performance of indicator is not so high level, the importance founding is that the component measured is suitable for developing brand.